KONTRIBUSI KONSEP DIRI DAN DUKUNGAN ORANGTUA TERHADAP MOTIVASI BELAJAR SISWA DAN IMPLIKASINYA DALAM PELAYANAN BIMBINGAN DAN KONSELING - Saragi, Muhammad Putra Dinata; Iswari, Mega; Mudjiran, Mudjiran (Universitas Negeri Padang, 2016)
The research was backgrounded by still low level of the learning motivation of students. The self-concept and parental support suspectted to affect the learning motivation of students. This research aims to describe : (1) the self-concepts, (2) parental support, (3) learning motivation of students, (4) the contribution of the self-concept toward the learning motivation of students, (5) the parental support contributions toward the learning motivation of students, and (6) the contribution of self-concept and parental support together against to the learning motivation of students. This study used a descriptive correlational quantitative method. The population of this research was students of SMA Negeri 8 Padang in class XI and XII which totaled 464 people. The number of samples are 215 people, selected by proportional stratified random sampling technique. The instrument used is the scale. Results validity and reliability of the instrument self-concept, parental support, and learning motivation of student stated that valid and reliable research instruments. Data were analyzed with descriptive statistics, simple regression, and multiple regression. The findings showed that: (1) the average description of self-concepts are in positive category, (2) an average description of parental support are in high category, (3) description of the learning motivation of students are in high category, (4) there is contribution of self-concept toward the learning motivation of students by 24.2%, (5) there is contribution of parental support toward the learning motivation of students by 18.8%, and (6) there are contributions of self-concept and parental support together toward the learning motivation of students amounted to 30.7%. Implications of the research results can be used as input to create a program of guidance and counseling services.